Benefit of triple-strap abdominal binder on voluntary cough in patients with spinal cord injury - Julia, P.E.; Sa'ari, M.Y.; Hasnan, N. (2011)
Study design: A cross-sectional experimental study. Objective: The purpose of this study is to examine the benefit of elastic abdominal binders on voluntary cough in persons with spinal cord injury. Setting: Spinal rehabilitation unit in a teaching hospital. Methods: We measured voluntary cough peak expiratory flow rate (in 21 subjects with spinal cord injury, (18 tetraplegia, 3 paraplegia) under three conditions: without abdominal binder as the baseline, with single-strap abdominal binder and triple-strap abdominal binder. Results: The results showed that the mean cough peak expiratory flow rate in all subjects without abdominal binder was 277.1 l per min. There was a significant increase in flow rate with the use of abdominal binders: 325.7 l per min with single-strap abdominal binder and 345.2 l per min with triple-strap abdominal binder (P < 0.05, paired t-test). The mean cough peak expiratory flow rate in tetraplegic subjects using triple-strap abdominal binders was significantly higher compared with those using single-strap abdominal binders (322.1 l per min and 299.4 l per min, respectively). Conclusion: Abdominal binders can be used as an effective method to improve cough ability in spinal cord injured patients, with triple-strap abdominal binder achieving greater cough peak expiratory flows. Spinal Cord (2011) 49, 1138-1142; doi: 10.1038/sc.2011.53; published online 17 May 2011